Performance Evaluation and Detection of Sybil Attacks in Vehicular Ad-Hoc Networks - Grover, Jyoti; Kumar, Deepak; Sargurunathan, M.; Gaur, M. S.; Laxmi, Vijay (Recent Trends in Network Security and Applications, 2010)
Vehicular Ad-hoc Networks (VANET) technology provides a fast, easy to deploy and an inexpensive solution for intelligent traffic control and traffic disaster preventive measure. In VANET, moving vehicles communicate using wireless technology. This communication can be used to divert traffic from congested or dysfunctional routes, to seek help in an emergency and to prevent accident escalation in addition to providing intelligent traffic control. However, an attacker can use the same system to spread false warning messages resulting in congestion on certain routes thereby leading to accidents or causing delay in providing help etc. One of the harmful attacks against VANET is Sybil attack, in which an attacker generates multiple identities to feign multiple nodes. In this paper, we present an implementation of simulated Sybil attack scenario in VANET and discuss its impact on network performance. A cooperative approach of Sybil attack detection, inferred through analysis of Sybil attack, is also presented.